Forensics mobile devices - Markagić, Milorad S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The article gives an overview of possibilities of digitized mobile(portable) devices, and methods of research data with them.Emphasis is placed on the forensic investigation of mobilephones, but are covered by other media and research for digitalprocessing, transmission and storage of information. A special emphasis was made on the software tools in carrying out the acquisition of digital data, with the aim of sending the reader on ways and methods to protect data but also knowledgewhich is the same all be found and how they can be misused for criminal purposes